2007
DOI: 10.1097/brs.0b013e318074c366
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy of rhBMP-2 for Posterolateral Lumbar Fusion in Smokers

Abstract: The results of this study suggest that rhBMP-2 may enhance fusion rate in cigarette smokers undergoing single-level instrumented posterolateral lumbar fusion. Despite the improvement in fusion rate with rhBMP-2, clinical outcomes measures were still adversely affected in smokers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
64
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(64 citation statements)
references
References 28 publications
0
64
0
Order By: Relevance
“…The authors of the original industry-sponsored or industry-associated studies of rhBMP-2 all reported the efficacy in applications including both anterior and posterior cervical and lumbar fusion surgery [3][4][5][6][7][8][9][10][11][12][13][14]. Additionally, the authors of these studies stated similar safety profiles with no adverse effects or complications attributable to rhBMP-2 in any study.…”
Section: Introductionmentioning
confidence: 67%
See 1 more Smart Citation
“…The authors of the original industry-sponsored or industry-associated studies of rhBMP-2 all reported the efficacy in applications including both anterior and posterior cervical and lumbar fusion surgery [3][4][5][6][7][8][9][10][11][12][13][14]. Additionally, the authors of these studies stated similar safety profiles with no adverse effects or complications attributable to rhBMP-2 in any study.…”
Section: Introductionmentioning
confidence: 67%
“…Institutional funds were received in support of this work. No benefits in any form have been or will be received from a commercial party related directly or indirectly to the subject of this manuscript" [12]. Furthermore, the accuracy of industry payment disclosure has significant incongruity.…”
Section: Recommendations Of Bias Classification In Scientific Publicamentioning
confidence: 99%
“…15,16 In terms of limitations of the study, we note the small sample size of the groups, making subgroup analysis in accordance with the different diagnoses impossible. In addition, the minimum time of postoperative follow-up considered for inclusion (six months) may be insufficient for the detection of fusion failures.…”
Section: Resultsmentioning
confidence: 99%
“…13,17 Early refinement had begun at the same time, such as in studies of rhBMP-2 for PLF specifically in adult spinal deformities and the effect of smoking on fusion. 16,20 Refinement increased and the total number of refinement studies surpassed the total number of initial studies, reaching PSA in 2007 (Fig. 3).…”
Section: Rhbmp-2 For Posterolateral Fusion-off-label Usementioning
confidence: 99%